The Great American Baseball Novel: How Literature Invented the National Pastime. (18th November 2022) - Darda, Joseph
Abstract: From 1846, when the Knickerbocker Base Ball Club lost their first game under a consolidated set of rules, transforming the "New York game" into "base ball, " and Walt Whitman, then a roving editor with the Brooklyn Eagle, observed neighborhood kids engaged in "a certain game of ball, " to the rise of television and football, literature elevated baseball from another bat-and-ball game to a national institution, a distorted mirror through which the nation identified itself. MLB commissioners and novelists have described baseball as a form of writing and as the literature of their childhoods because the game first achieved national status through writing and literature. From Whitman to Bernard Malamud, American authors turned to baseball to determine the health of the nation, encouraging their readers to invest in the health of the game. First came the great American baseball novel, then the national pastime.Baseball nationalism needed the hard sell of sportswriters and the soft touch of literature.